Effect Of Medial Arch Support On Valgus Ankle Angle In Flat Foot Conditions - Adinda Imas Nicavia; Yopi Harwinanda Ardesa; Muhibbah Fatati (Poltekkes Kemenkes Surakarta, 2022)
Background: Flat foot, or pes planus, is a condition where the medial longitudinal arch is lost, resulting in flat feet. In this case, if there is a problem with the medial longitudinal arch, it will affect the joint above it, called the valgus ankle. Handling flat foot is done by providing medial arch support. The use of medial arch support aims to maintain the foot and ankle in a neutral position by supporting the medial part so that the valgus can be corrected. Methods: This type of research is a quasi-experiment with a one-group pre- and post-test design. The number of subjects was 32 students of the Applied Undergraduate Program, Department of Prosthetic Orthotics. Results: Using the Wilcoxon hypothesis test and the p-value was found to be 0.000 for the right and left pre- and post-test foot. This shows that there is a decrease in the ankle valgus angle before and after the use of medial arch support. The average decrease in valgus ankle angle between pre- and post-test on the right foot was 2.32 degrees, while it was 2.44 degrees on the left foot. Conclusion: The use of medial arch support has an effect on decreasing valgus ankle in flat foot conditions, so it is recommended to use medial arch support in flat foot conditions.